Pelatihan Pembuatan Laporan Keuangan Usaha Rumahan UMKM Tunas Muda Olahan Keripik dan Peyek Kec. Air Periukan Kab. Seluma Bengkulu - Sari, Risna Purnama; Sudarsono , Aji; Astuty , Kamelia (Universitas Dehasen Bengkulu, 2025)
Financial reports are information that describes the condition of a financial company and becomes a description of the business's financial performance. It is also undeniable that the Tunas Muda MSME home business really needs financial reports because there are many uses if we make financial reports, such as easily controlling all operational costs in the Young Tunas business and being able to determine the selling price of the product and profit and loss from the Young Tunas business. This Tunas Muda MSME business plays an important role in the world of the traditional food business in Seluma Regency, therefore proper business planning is needed for the future, such as being able to recruit employees. money in the bank, to steal money in the bank, a financial recording report is needed because one of the conditions is to have a complete financial report. In this regard, an approach / training will be carried out in preparing financial reports for the Young Tunas MSME business. The purpose of this training is to assist Young Tunas business actors in controlling the finances of their business so that it facilitates the process of modifying this business and Young Tunas businesses will continue to increase in the future.